PENGARUH KEPEMIMPINAN, KEPUASAN KERJA DAN DISIPLIN KERJA TERHADAP PRODUKTIFITAS GURU - Budiyanto, Ruddy; Dwiatmadja, Christantius; Rusdianti, Endang (Sustainable Business Journal, 2024)
This research aims at testing and analyzing the influence of leadership, working satisfaction and working discipline towards teachers’ productivity; testing and analyzing the influence of leadership, working satisfaction and working discipline towards teachers’ productivity with organization commitment as the intervening variable. This research is using quantitative approach. The data testing technique being used in this research including validity test with pearson correlation, reliability test with cronbach alpha, classical assumption test including normality test, heteroscedasticities and multicollinearities test, double regression analysis, signification test and determination coefficient test to prove the validity and rightness of the research hypothesis. From the results of the study, it was found that leadership, job satisfaction and work discipline had a significant effect on organizational commitment. In addition, leadership, job satisfaction and work discipline have a significant effect on teacher productivity. And organizational commitment has a significant effect on teacher productivitycontribution towards teachers’ productivityTujuan penelitian ini adalah menguji dan menganalisis pengaruh kepemimpinan, kepuasan kerja dan disiplin kerja terhadap produktivitas  guru, menguji dan menganalisis pengaruh kepemimpinan, kepuasan kerja dan disiplin kerja terhadap produktivitas guru dengan komitmen organisasi sebagai variabel intervening.  Penelitian ini menggunakan pendekatan kuantitatif. Teknik pengujian data yang digunakan dalam penelitian ini meliputi uji validitas dengan pearson correlation, uji reliabilitas dengan cronbach alpha, uji asumsi klasik meliputi uji normalitas, uji heteroskedastisitas, dan uji multikolinieritas, analisis regresi berganda, uji signifikansi dan uji koefisien determinasi untuk membuktikan keabsahan dan kebenaran hipotesis penelitian. Dari hasil penelitian diperoleh bahwa kepemimpinan, kepuasan kerja dan disiplin kerja  berpengaruh signifikan terhadap komitmen organisasi. Selain itu, kepemimpinan, kepuasan kerja dan disiplin kerja berpengaruh signifikan terhadap produktivitas guru. Dan komitmen organisasi berpegaruh signifikan terhadap produktivitas guru